2011
DOI: 10.1177/1010539510373139
|View full text |Cite
|
Sign up to set email alerts
|

Residential Environmental Risk Factors for Childhood Asthma Prevalence in Metropolitan and Semirural Cities in Korea

Abstract: To identify the association between residential environmental risk factors and the prevalence of childhood asthma, the authors surveyed the prevalence of asthma, the residential environmental risk factors of 1819 elementary school students, and air pollution in metropolitan (Seongbuk), and semirural (Andong) areas. Although there was no significant difference in the prevalence of self-reported asthma (SA) between the 2 geographic areas (12.8% vs 13.6%), the prevalence of physician-diagnosed asthma (PDA) in And… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 21 publications
(25 reference statements)
2
17
1
Order By: Relevance
“…In this study, household income had a significant association with asthma but parents’ education did not. A similar result has already shown in other study in Korea [20]. For this finding, authors of the previous study suggested that that the hierarchical difference according to the education level may be not significant due to the high enthusiasm for education–the entrance rate into the college is over 80%–in Korea [20].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In this study, household income had a significant association with asthma but parents’ education did not. A similar result has already shown in other study in Korea [20]. For this finding, authors of the previous study suggested that that the hierarchical difference according to the education level may be not significant due to the high enthusiasm for education–the entrance rate into the college is over 80%–in Korea [20].…”
Section: Discussionsupporting
confidence: 85%
“…A similar result has already shown in other study in Korea [20]. For this finding, authors of the previous study suggested that that the hierarchical difference according to the education level may be not significant due to the high enthusiasm for education–the entrance rate into the college is over 80%–in Korea [20]. Differences in the distribution of allergic diseases by region indicate differences in the level of environmental exposure and socioeconomic status [21].…”
Section: Discussionsupporting
confidence: 78%
“…Interestingly, the ISAAC results in 2010 with first-grade students showed that the asthma prevalence rate was higher in rural than in urban areas [ 4 ]. A recent study revealed that the asthma prevalence rate in semi-rural areas such as Andong was higher than that in Seoul, and if potentially hazardous industrial facilities were located near a residential area, the OR for asthma could increase [ 31 ]. The prevalence rates for allergic diseases are related to the level of exposure to toxic airborne chemicals such as sulfur dioxide, carbon monoxide or nitrogen dioxide [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a Korean study that looked at 1819 elementary school students, and air pollution in metropolitan (Seongbuk), and semirural (Andong) areas found no significant difference in the prevalence of self-reported asthma. 15…”
Section: An Urban Versus Rural Phenomenonmentioning
confidence: 99%